2011
DOI: 10.4103/0972-0707.80725
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of microbial leakage in roots filled with resilon and gutta-percha: An in vitro study

Abstract: Background and Objective:The objective of this study was to compare bacterial leakage using streptococcus mutans through gutta-percha and a thermoplastic synthetic polymer based root canal filling material (Resilon) using two filling techniques.Materials and Methods:A total of 90 single-rooted extracted human teeth were subjected for the study. Teeth were divided into 6 groups of 10 and 3 control groups of 10 teeth each. All the samples were decoronated and the coronal surfaces of the roots were prepared perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Gutta-percha used with sealers fail to seal the dentinal wall. 4 Although the resin-based sealers in Resilon could effectively penetrate the dentinal tubules in moist dentin, they are still susceptible to the effects of matrix metalloproteinase in the dentin matrix. 21,22 In contrast, MTA has been shown to resist leakage at a higher rate when placed in a moist environment such as the root canal system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gutta-percha used with sealers fail to seal the dentinal wall. 4 Although the resin-based sealers in Resilon could effectively penetrate the dentinal tubules in moist dentin, they are still susceptible to the effects of matrix metalloproteinase in the dentin matrix. 21,22 In contrast, MTA has been shown to resist leakage at a higher rate when placed in a moist environment such as the root canal system.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed that current root canal obturation materials such as gutta-percha and/or polymer-based materials cannot provide a bacteria-tight seal. 3,4,5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Various in-vitro studies showed that gutta-percha fillings leak at a rapid rate[ 15 16 ] and do not result in a dependable seal over a long term period. [ 17 ] In this study, it was found that the gutta-percha leakage increased with time whereas Resilon + Epiphany not only produced a superior seal but also maintained it over all time intervals. Studies have been conducted previously comparing the physical properties of gutta-percha and Resilon which observed that the shrinkage of Resilon is only 0.5% after application of heat when compared with gutta-percha, which shrinks 5–7%.…”
Section: Discussionmentioning
confidence: 74%
“…13 Xylene is an aromatic organic solvent and allows better control of gutta percha during removal as it slowly softens rather than dissolve gutta percha. 14,15 This can be accomplished by placing a cotton pellet dipped in the material inside the pulp chamber and removing the gutta percha on the following visit. This holds especially true for aged gutta percha as it tends to get very hard and difficult to remove.…”
Section: Discussionmentioning
confidence: 99%